2007
DOI: 10.1080/02791072.2007.10400611
|View full text |Cite
|
Sign up to set email alerts
|

Substance Abuse Treatment Staff Perceptions of Intimate Partner Victimization Among Female Clients

Abstract: Providing intimate partner violence (IPV)-related services to women enrolled in substance abuse treatment programs has the potential to reach a population disproportionately affected by IPV. Integrating basic IPV services into substance abuse treatment, however, poses challenges to organizations and staff. Using focus groups, the authors examined the experiences and attitudes of substance abuse treatment staff towards clients with IPV victimization experiences in order to elucidate factors that might affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
(12 reference statements)
1
16
0
Order By: Relevance
“…A study among staff in Canada found that when accessing health and harm reduction services, people with experience of intimate partner violence encounter stigmatising or victim-blaming attitudes [ 55 ]. Under-resourced staff, both in terms of training and high caseloads, reduces the likelihood that intimate partner violence will be addressed [ 58 ]. The lack of services for people with experience of intimate partner violence is an unmet need in harm reduction services.…”
Section: Methodsmentioning
confidence: 99%
“…A study among staff in Canada found that when accessing health and harm reduction services, people with experience of intimate partner violence encounter stigmatising or victim-blaming attitudes [ 55 ]. Under-resourced staff, both in terms of training and high caseloads, reduces the likelihood that intimate partner violence will be addressed [ 58 ]. The lack of services for people with experience of intimate partner violence is an unmet need in harm reduction services.…”
Section: Methodsmentioning
confidence: 99%
“…These barriers include overburdened staff, lack of private screening space, lack of reimbursement for services, lack of adequate training of staff, lack of access to IPV referrals, and perceived lack of confidentiality. 28,29 Given the multiple barriers for providers screening for IPV and substance use in emergency or primary care settings, there may be significant advantages to using self-paced computerized IPV screening tools. Accumulating research among women in health care settings has found that selfpaced computerized screening interviews are effective in increasing rates of IPV disclosure.…”
Section: Ipv and Suds: Mental And Physical Health Comorbiditiesmentioning
confidence: 99%
“…This may be explained by high counselor caseloads, a lack of training of program staff to assess for IPV, few resources, and a scarcity of treatment approaches in substance abuse programs to deal with IPV (Kunins, Gilbert, Whyte, Meissner, & Zachary, 2007). Referrals may not occur because the number of IPV treatment programs or battered women's shelters that will accept drug-involved women is low.…”
Section: Challenges Drug Treatment Programs Face In Dealing With Ipv mentioning
confidence: 99%